integration

Asked by  | 24th Jan, 2009, 12:59: AM

Expert Answer:

multiply numinator and denominator with undre root sin x  and write sin x as  1 - cos 2 x   so the final integration is  I = sin x /  (sin x)  =  sin x  dx /  ( 1 - cos 2 x  )    

now let cos x = t  ===>  - sinx dx = dt ===> I = - dt /  (1 - t 2)   ====>  I = sin -1 t =  - sin -1 (cos x )

Answered by  | 29th Jan, 2009, 05:41: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.